Venezuelans in Argentina, the United States and Portugal: a diaspora on the making - Padilla, Beatriz (2021)
In this article, we argue that recent Venezuelan migration is a diaspora on the making. Based on participant observations and interviews with key informants and Venezuelan immigrants living in Argentina, the United States (Florida), and Portugal, we establish that the shared experience arising from the humanitarian crisis in their country of origin, and their common transnational reality is contributing to the process institutionalization and consolidation ofthe Venezuelan diaspora.